2021
DOI: 10.1371/journal.pbio.3001325
|View full text |Cite
|
Sign up to set email alerts
|

Predicting learning and achievement using GABA and glutamate concentrations in human development

Abstract: Previous research has highlighted the role of glutamate and gamma-aminobutyric acid (GABA) in learning and plasticity. What is currently unknown is how this knowledge translates to real-life complex cognitive abilities that emerge slowly and how the link between these neurotransmitters and human learning and plasticity is shaped by development. While some have suggested a generic role of glutamate and GABA in learning and plasticity, others have hypothesized that their involvement shapes sensitive periods duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 86 publications
3
39
0
Order By: Relevance
“…The traditional analyzing method could have partially captured aperiodic activity, which is thought to relate to the E/I in the brain which subsequently underlies learning (Zacharopoulos et al, 2021). The magnetic resonance spectroscopy (MRS) study from Zacharopoulos et al (2021) found that decreased E/I leads to enhanced mathematical skill in the developing brain, and that the opposite happens in the adult brain. Note that our study found exactly the opposite as Zacharopoulos and colleagues (2021) for children, which might be due to MRS and EEG differences that capture different aspect of E/I.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The traditional analyzing method could have partially captured aperiodic activity, which is thought to relate to the E/I in the brain which subsequently underlies learning (Zacharopoulos et al, 2021). The magnetic resonance spectroscopy (MRS) study from Zacharopoulos et al (2021) found that decreased E/I leads to enhanced mathematical skill in the developing brain, and that the opposite happens in the adult brain. Note that our study found exactly the opposite as Zacharopoulos and colleagues (2021) for children, which might be due to MRS and EEG differences that capture different aspect of E/I.…”
Section: Discussionmentioning
confidence: 99%
“…The magnetic resonance spectroscopy (MRS) study from Zacharopoulos et al (2021) found that decreased E/I leads to enhanced mathematical skill in the developing brain, and that the opposite happens in the adult brain. Note that our study found exactly the opposite as Zacharopoulos and colleagues (2021) for children, which might be due to MRS and EEG differences that capture different aspect of E/I. A recent finding from our lab supports this notion by showing that mathematical learning can influence the aperiodic exponent (i.e., E/I) and that an excitatory form of neurostimulation can influence this directly (Van Bueren et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After evaluating the subjects twice and 1.5 years apart, the researchers discovered that adults with reduced GABA performed well on the first arithmetic exam and also performed well on the second test. 3,6 What does exactly findings mean? The longitudinal approach used by the scientists aided them in forecasting future mathematical aptitude.…”
Section: What Are Their Study Findings?mentioning
confidence: 99%